PENINGKATAN HASIL BELAJAR SISWA PADA MATERI KONSEP MOL DENGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DI KELAS XI SMA - Togi Pangihutan Tua Siahaan; Enjelita Maharaja; Gustini Renti Lidia Siburian; Helena Sitinjak; Muhammad Andra Febrian Siregar; Putri Andini; Marnida Yusfiani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is motivated by the low chemistry learning outcomes of students on the Mole Concept material at SMA Negeri 2 Percut Sei Tuan. The Mole Concept, which is abstract and complex in nature, is often considered difficult and boring by students, compounded by the use of one-directional conventional learning methods that make students passive and less motivated. To address this problem, an innovation was carried out through the application of the Problem Based Learning (PBL) model integrated with video media. This study aims to improve student learning outcomes on the Mole Concept material through the implementation of the PBL model. The research method used is Classroom Action Research (CAR) conducted in two cycles, where each cycle consists of four main stages: planning, acting, observing, and reflecting. The research subjects were 35 students of class XI-C at SMA Negeri 2 Percut Sei Tuan for the 2025/2026 academic year. Data collection instruments included learning outcome tests (pretest and posttest) to measure students' cognitive competence, and observation sheets to monitor student activities and teacher performance. The results showed that the application of the PBL model integrated with video media significantly improved student learning outcomes, with classical completeness reaching 85% or more in cycle II and the average N-Gain score in the moderate to high category.